(untitled) (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: Antibiotic resistance has become a global public health concern. Thus, the objectives of this study was to determine the overall knowledge of drugs and explore the level of awareness of antibiotic resistance among students studying at Jahangir-Nagar University, Bangladesh. Material and Methods: The total period of sample collection was from June 2018 to October 2018 and the participants (was N=100). This descriptive cross-sectional study used a questionnaire that consisted of fifteen close ended questions and specific questions were on background (gender, age, education) characteristics. Descriptive statistics (frequency, distribution, mean and standard deviation was used to describe the data. The data collected from the 100 students nd analyzed by statistical tools (SPSS V.22) by drawing tables and graphs. Results: Overall, 100 female students (age from 19 to 24 years) were interviewed and the response rate was 100%. Out of total respondents, around 86% of the sample stated that antibiotics are appropriate for bacterial infections and 34% of the students had agreed antibiotic can cure viral infections. 74% of the respondents hadn’t expected antibiotics when they had enough with cold, fever, cough and sore throat. Some had taken without prescription. Almost above 90% of the students stop taking those drugs when symptoms decrease and do not take full dose. About 91% respondent agreed to the need of more education about antibiotic resistance. Conclusion: It is important to generate more awareness around this issue among all. It would be advisable to introduce a specific course and training on antibiotics in core curriculum of students.